ASUHAN KEPERAWATAN PADA KLIEN STROKE NON HEMORAGIK DENGAN RISIKO PERFUSI SEREBRAL TIDAK EFEKTIF DAN GANGGUAN MOBILITAS FISIK - Adinda Maulina Piliang (2023)
Background: Non-hemorrhagic stroke is a stroke that occurs when a blood clot narrows an artery leading to the brain, this is caused by high blood pressure. More than 13 million people suffer strokes each year, making it the second leading cause of death and disability in the world. After the first attack, strokes can occur again with more severe conditions. Purpose: This research was conducted to provide education and skills in implementing nursing care for non-hemorrhagic stroke clients with the risk of ineffective cerebral perfusion and impaired physical mobility. Methods: The design of this case study is made in the form of a case report oriented to the nursing process approach method, where data collection is carried out by interviews, observation and physical examination, and documentation studies. Results: The nursing problems found in this case are the risk of ineffective cerebral perfusion, impaired physical mobility, and ineffective health management. The main nursing action taken is to provide education on PATUH behavior and ROM exercises. Conclusion: After nursing actions for 3x24 hours, one of the three diagnoses that appeared has been resolved, while the other 2 have not been resolved properly, due to limited research time. Suggestion: It is hoped that future researchers can estimate the research time properly so that clients achieve maximum results. Keywords: Nursing Care, Non-Hemorrhagic Stroke, Risk of Ineffective Cerebral Perfusion, Impaired Physical Mobility